UPAYA PENINGKATAN SARANA DAN PRASARANA DALAM MENINGKATKAN MINAT BELAJAR SISWA DI MTsN 9 BIREUEN - Anwar Ebtadi; Wiene Surya Putra (Jurnal Tarbiyah Almuslim, 2023)
This research aims to find out the general description of MTsN 9 Bireuen, to find out the obstacles and solutions faced in improving facilities and infrastructure in increasing students' interest in learning at MTsN 9 Bireuen. This research uses qualitative research with the type of field research. Data analysis was carried out in three stages, namely reduction, display, verification. The research findings inform that: first, the general description of MTsN 9 Bireuen is that it is one of the madrasas in the district. Bireuen and founded. Based on the decision of the Minister of Religion of the Republic of Indonesia, Dr. H. Tarmizi Thahir issued decree number 107 of 1997 dated March 17 1997 which stipulated the designation of MTsN Kutablang as Madrasah Tsanawiah Negeri 9 Bireuen, North Aceh Regency (formerly). Second, the obstacles faced in improving facilities and infrastructure at MTsN 9 Bireuen include the following: the school budget, lack of tools and learning media, only a few percent of the school budget provided by the government is used, limited numbers and expertise. executor in facility maintenance. Third, internal efforts to improve facilities and infrastructure to increase students' interest in learning at MTsN 9 Bireuen consist of: the efforts of the principal, deputy principal, teachers and students. Efforts made by external parties consist of: the efforts of the school committee, student guardians, institutions, the community.